2018
DOI: 10.22146/jcoemph.39156
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan timbal dan krom pada pemakaian pewarna batik dengan kadar hemoglobin dan packed cell volume pada pengrajin batik di Kecamatan Lendah Kulon Progo

Abstract: ABSTRAK Cara membatik di Indonesia mulai banyak beralih dari pemakaian bahan alami menjadi bahan cat sintesis. Cat sintetis yang digunakan sering kali mengandung logam berat di antaranya timbal (Pb) dan kromium (Cr). Pemakaian logam berat dalam waktu lama akan mengganggu kesehatan. Penelitian ini dilakukan untuk melihat hubungan kadar logam Pb dan Cr dalam darah dan limbah dengan kadar hemoglobin (Hb) dan Packed Cell Volume (PCV) serta mengetahui prevalensi gejala toksisitas yang dirasakan pada pekerja di tiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
2
0
3
Order By: Relevance
“…Participant’s jobs were categorized as lead-exposed occupations if they reported conducting canting (a traditional hand-drawing method on fabric using liquid wax and dye), dipping the fabric in the dye, and washing the fabric after the coloring process because our prior study found excessive lead concentration in batik workers’ inhaled air during these processes at the workplaces [ 7 ]. A previous study found that participants who had these jobs were found to have elevated blood lead levels because they were exposed to synthetic dye-containing lead [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…Participant’s jobs were categorized as lead-exposed occupations if they reported conducting canting (a traditional hand-drawing method on fabric using liquid wax and dye), dipping the fabric in the dye, and washing the fabric after the coloring process because our prior study found excessive lead concentration in batik workers’ inhaled air during these processes at the workplaces [ 7 ]. A previous study found that participants who had these jobs were found to have elevated blood lead levels because they were exposed to synthetic dye-containing lead [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…Terdapat sekitar 10 sampai 13% dari kayu yang di gergaji akan berbentuk debu kayu. Pola aktivitas sehari-hari dan faktor penyerta yang potensial seperti umur, jenis kelamin, etnis, kebiasaan merokok dan faktor allergen (Hastuti et al, 2018). Gangguan pernafasan merupakan kondisi tidak normal yaitu ada kelainan satu atau lebih berupa batuk pilek disertai dahak/tidak, napas cepat baik disertai demam atau tidak (Muliadi, 2015).…”
Section: Hubungan Usia Dengan Gejala Batuk Pada Pekerja Industri Tenu...unclassified
“…On the other hand, with regard to the potential risk of exposure, batik industry have a potential risk of heavy metal exposure through various portal of entry including through skin (dermal) [11], inhalation, and oral [12]. Heavy metal -containing dyes were detected in Batik wastewater and also in workers exposure [13]. Health impact of heavy metal exposure has been revealed by various studies including effect on nervous system [14].…”
Section: Introductionmentioning
confidence: 99%